The Effectiveness of Teachers’ Performance in Implementing the Merdeka Curriculum at SDN 1 Lubuk Seberuk - Siti Maisaroh; Nur Ahyani; Suherman Suherman (International Journal of Educational Development, 2025)
In addition to the main aspects of teacher competency, the study also emphasizes the importance of leadership and institutional support in the effective implementation of policies. The school leadership plays a crucial role in creating a conducive environment for professional development, fostering a culture of collaboration among teachers, and ensuring the implementation of competency-based assessments. It was found that the active involvement of the principal in monitoring and providing feedback to teachers significantly contributes to the continuous improvement of teaching practices. The study also highlights the importance of aligning teacher competency development with the school's educational goals and objectives. While some teachers have demonstrated significant improvement in their teaching methods and student engagement, others still require more support to fully integrate the competencies into their daily practices. The continuous professional development of teachers is therefore vital to ensure that the competencies are not only understood but also consistently applied in the classroom. Moreover, the study recognizes the critical role of community and parental involvement in enhancing the quality of education. Collaboration between the school, parents, and the local community can create a more supportive learning environment, ensuring that students receive the necessary resources and encouragement both at school and at home. In conclusion, the research suggests that while the implementation of teacher competency policies at SDN 2 Lubuk Seberuk has shown positive results, the process should be supported with more training opportunities, resource allocation, and consistent monitoring to overcome existing challenges.